Properties of L=1 B1 and B2* mesons - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
This Letter presents the first strong evidence for the resolution of the excited B mesons B1 and B2* as two separate states in fully reconstructed decays to B+(*)Ï€-. The mass of B1 is measured to be 5720.6Â.±2.4Â.±1.4Â.€‰Â.€ ‰MeV/c2 and the mass difference ÎM between B2* and B1 is 26.2Â.±3.1Â.±0. 9Â.€‰Â.€‰MeV/c2, giving the mass of the B2* as 5746.8Â.±2.4Â.±1. 7Â.€‰Â.€‰MeV/c2. The production rate for B1 and B2* mesons is determined to be a fraction (13.9Â.±1. 9Â.±3.2)% of the production rate of the B+ meson. © 2007 The American Physical Society.